TRIM25 has a dual function in the p53/Mdm2 circuit - Zhang, Ping; Yan, Hualong; Wittbrodt, Joachim (Oncogene, 2015)
Oncogene is one of the world’s leading cancer journals. It is published weekly and covers all aspects of the structure and function of Oncogenes.